Evaluating black women’s participation, development and success in doctoral studies: A capabilities perspective - Loots, S; Ts'ephe, L; Walker, M (South African Journal of Higher Education, 2016)
Although black women show an increased presence in doctoral study, the probability of intersecting gendered and racial disadvantage is often overlooked through relying on separate numerical transformation progress indicators for gender and race. To take a more active approach to furthering social justice for this marginalised group, we need to explore more holistic ways of mapping transformation. In this sense, we argue for the application of the capabilities approach as an evaluative framework which allows for an assessment of freedoms or capabilities students are able to make use of in pursuing the lives they have reason to value. Furthermore, factors impacting on students’ capability formation are also considered, thus providing a multidimensional, ethically individualistic exploration of lives. The experiences of seven black women speak of barriers they have experienced throughout their doctoral journeys, but the data also create a sense of optimism as the potential of capability expansion is addressed.